The diagnosis and treatment of a special rare type of Monteggia equivalent fractures in children - Fei Su; Fei Su; Fei Su; Min Li; Min Li; Min Li; Yishan Ma; Yishan Ma; Yishan Ma; Yating Yang; Yating Yang; Yating Yang; et al. (Frontiers Media S.A., 2023)
PurposeTo explore the characteristics, mechanism, treatment, and prognosis of head-neck separation type of Monteggia equivalent fractures in children.MethodsPatients with this injury were reviewed retrospectively. The lesion was characterized by a fracture of the ulnar with radial neck fracture but without dislocation of the radial head. Our classification was based on the direction of displacement and angulation of fractures on radiographs, divided into the extension-valgus type and flexion-varus type. The fractures were treated with reduction and internal fixation, depending on the fracture type. The clinical results were evaluated by using radiology and the Mayo Elbow Performance Score (MEPS).ResultsA total of 12 patients were followed up for an average of 40.5 months. The ulnar fractures were treated with closed reduction (CR) and K-wire fixation in one patient, elastic stable intramedullary nail (ESIN) fixation in four patients, open reduction (OR) and plate fixation in five, with no fixation in two. CR with ESIN fixation was successful in 11 patients with radial neck fractures, but one underwent OR and K-wire fixation. All fractures healed on time, with fewer complications (avascular necrosis in one patient, and bulk formation of metaphysis in another). The therapeutic efficacy was evaluated by using MEPS and was found to be excellent in 10 patients, good in one, and fair in another.ConclusionsThe head-neck separation type of Monteggia equivalent fractures in children is rare. Its characteristics are different from that of Monteggia fracture. The length and anatomic structure of the ulna should be restored and stabilized first, while the radial neck fracture should be treated with CR and ESIN fixation. Satisfactory clinical results can be achieved with fewer complications.